Analysis of energy recovery system for buildings in Singapore tropical climate - Yong, Yao Jun (2017)
Owing to a hot and humid tropical climate of Singapore, Heating, Ventilation and Air-Conditioning (HVAC) systems are widely used to cool the building’s indoor temperature to achieve thermal comfort for its occupants. The building sector is currently one of the largest energy-consuming sector, and a huge portion of it are attributed to HVAC systems alone due to its high energy consumption rate. In order to curb the building cooling load in Singapore, energy recovery technologies have to be used to mitigate the high energy consumption of HVAC without reducing the indoor air quality. The purpose of this project was to evaluate how the performance of a fixed-plate cross-counter flow Membrane-based Energy Recovery Ventilator (MERV) has on the potential cooling energy savings in a hot and humid climate. The outdoor air was simulated using a humidifier and a heater to the outdoor condition. The sensible, latent and enthalpy efficiencies of such a system was also being investigated. Several varying parameters such as velocity, temperature and humidity of the airflows were used for the experimental analysis. Both balanced and unbalanced flow were analysed. The experimental data were obtained from sensors installed around the MERV with the help of a data acquisition (DAQ) device. Results of the experiment shows that for balanced flow, enthalpy efficiency of the MERV increases with higher outdoor air (OA) temperature and difference in humidity ratio between OA and return air (RA). Higher OA temperature means a higher sensible efficiency while a higher difference in humidity ratio means a higher latent efficiency. However, efficiencies decrease with increasing fan velocity. Total energy savings increases with higher OA temperature, difference in humidity ratio and fan velocity. For balanced flow, highest savings of 1,169.30W is achieved at difference in humidity ratio of 6.22g/kg, OA temperature of 35.02°C and fan velocity of 3.0m/s. For unbalanced flow, efficiencies increase with higher exhaust fan velocity and lower supply fan velocity. Enthalpy efficiency increases with lower OA temperature. For unbalanced flow, total energy savings increases with higher exhaust and supply fan velocity, and a higher difference in humidity ratio. The highest savings for unbalanced flow is achieved at 885.19W at supply fan velocity of 2.5m/s, exhaust fan velocity of 3.0m/s for 6g/kg difference in humidity ratio and OA temperature of 30°C. ERV is a viable option for energy savings in Singapore’s tropical climate as optimum efficiencies are more than 80%. Even though the payback cost of an ERV is about 1 year to 6 years, it is still effective due to the high HVAC usage in Singapore.